Data for: Comparative genomics of abiotic stress response in Norway spruce and Scots pine - van Zalen, Elena M.; Canovi, Camilla; Kumar, Vikash; Chapple, Ellen Dimmen; Castro, David; Viljamaa, Sonja; Hvidsten, Torgeir R.; Hurry, Vaughan; Street, Nathaniel (Umeå University, 2026)
Data and analysis outputs supporting the comparative genomics manuscript on abiotic stress co-expression in Picea abies and Pinus sylvestris. Includes expression matrices for cold and drought stress conditions, differential expression results, annotation and sample metadata, and the ComPlEx co-expression network output (co-expressolog pairs and weighted gene pairs). Analysis code is available in the associated GitHub repository, see Related Materials.
Keywords: Biological network analysis; Genomics and transcriptomics; Statistical and quantitative genetics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik